Effect of Music on Personality: - A Experimental Study of UG Students - Rajesh Patgaonkar, Smita; M. Thik, Sonali (Journal of Neonatal Surgery, 2025)
Listening to music in everyday life has become common practice in college students. Since music helped them in different ways, but we all had seen students’ plugin their earphones throughout the day, they might be doing this for some other reasons. But most commonly it is seen, they do it for listening to music. So here it is necessary to test whether it is beneficial to the students or not. The overall objective of the study was to find the effect of listening to music on their personality and whether this trend is helped the students to improve their personality. A random sample of 50 UG students are selected who are interested in listening to music. The study comprised of two phases of survey namely questionnaire based and experimental based. Under questionnaire based, data is collected about students’ perception about listening to music. The experimental based study is carried out in a closed class room where music is played on three different days with three different decibels (Low = 60 to 70, Normal= 70 to 80 & High=80 to100) and observations were recorded. Special guidance is taken from the psychology department to measure the personality score. Personality scores were noted down on five different personality traits namely Openness, Extroversion, Consciousness, Agreeableness and Neuroticism. A Present study tries to find out the effect of listening to music on personality of UG students. Here we have done the comparative analysis of pre and post observations of different personality traits and health issues. In short, this paper wants to explore whether listening to music is beneficial to the students to improve their personality and if yes, in what way? Also, the study assesses the health issues faced by them after listening to music.